Chemical and microbiological changes in Norway spruce deadwood during the early stage of decomposition as a function of exposure in an alpine setting. Issue 1 (1st January 2018) - Bardelli, Tommaso; Gómez-Brandón, María; Fornasier, Flavio; Arfaioli, Paola; Egli, Markus; Pietramellara, Giacomo; Ceccherini, Maria Teresa; Insam, Heribert; Ascher-Jenull, Judith
ABSTRACT: Alpine ecosystems are vulnerable to ever-changing environmental conditions, leading to shifts in vegetation distribution and composition with implications on soil functionality and carbon (C) turnover. Although deadwood represents an important global C stock, scarce information is available on how slope exposure influences the wood-inhabiting microbiota throughout the decomposition process in an Alpine setting. We therefore evaluated the impact of slope exposure (north- vs . south-facing sites) on physicochemical and microbiological properties (microbial abundance based on real-time PCR: fungal 18S rRNA, dinitrogen reductase [ nifH ]; microbial biomass: double strand DNA; and microbial activity: hydrolytic enzyme activities of the main nutrient cycles) of Picea abies wood blocks and the underlying soil in a field experiment in the Italian Alps during a three-year period. Overall, a higher abundance of fungi and nitrogen-fixing bacteria was recorded in the soil at the north-facing site where cooler and moister conditions were observed. In contrast, no exposure effects were found for these two microbial groups in the wood blocks, while their abundance increased over time, accompanied by more acidic conditions with progressing decay. The impact of exposure was also enzyme specific and time dependent for both the P. abies wood blocks and the underlying soil.